Trans-disciplinary research on religious formations in urban Africa: Towards liberative methodological approaches - Beer, Stephan F. de (HTS teologiese studies, 2017)
In this article, we are exploring a methodological approach to research on faith and religious expressions in urban Africa. We are committed to trans-disciplinary work that pursues research methods mutually liberating for researchers, co-researchers and community participants and that results in long-term benefits and strengthened agency on the part of the host communities. Our reflections in this article are based on a collaborative research project1 in two regions of Pretoria, Tshwane2 – Pretoria Central and Mamelodi East – in which we explore how religious innovation and competition in and amongst churches contribute to the healing or perpetuation of urban fractures.